Demonstration of Transmission Mode Soft X-ray NEXAFS Using Third- and Fifth-Order Harmonics of FEL Radiation at SACLA BL1 - Hiroshi Iwayama; Masanari Nagasaka; Ichiro Inoue; Shigeki Owada; Makina Yabashi; James R. Harries (Applied Sciences, 2020)
We demonstrate the applicability of third- and fifth-order harmonics of free-electron laser (FEL) radiation for soft X-ray absorption spectroscopy in the transmission mode at SACLA BL1, which covers a photon energy range of 20 to 150 eV in the fundamental FEL radiation. By using the third- and fifth-order harmonics of the FEL radiation, we successfully recorded near-edge X-ray absorption fine structure (NEXAFS) spectra for Ar 2p core ionization and CO2 C 1s and O 1s core ionizations. Our results show that the utilization of third- and fifth-order harmonics can significantly extend the available photon energies for NEXAFS spectroscopy using an FEL and opens the door to femtosecond pump-probe NEXAFS using a soft X-ray FEL.